The production of calcium and magnesium during pancreatic function tests in health and disease. Issue 2 (February 1970) - Nimmo, J.; Finlayson, N. D. C.; Smith, A. F.; Shearman, D. J. C.
Abstract : Duodenal calcium and magnesium concentrations after pancreatic stimulation were measured in 25 patients with and without pancreatic disease. The concentration of both ions was higher in those with pancreatic disease, and furthermore these patients showed a different secretory pattern. These findings may be relevant to the aetiology of pancreatitis and to pancreatic calcification, and might be of diagnostic value.